2021
DOI: 10.1111/nmo.14095
|View full text |Cite
|
Sign up to set email alerts
|

Of bowels, brain and behavior: A role for the gut microbiota in psychiatric comorbidities in irritable bowel syndrome

Abstract: Background:The gastrointestinal microbiota has emerged as a key regulator of gutbrain axis signalling with important implications for neurogastroenterology. There is continuous bidirectional communication between the gut and the brain facilitated by neuronal, endocrine, metabolic, and immune pathways. The microbiota influences these signalling pathways via several mechanisms. Studies have shown compositional and functional alterations in the gut microbiota in stress-related psychiatric disorders. Gut microbiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 140 publications
(275 reference statements)
0
14
0
Order By: Relevance
“…With further research on IBS and the development of the theory of microbiota–gut–brain axis, the intestinal microbiota has been suggested as the pathophysiological basis of functional gastrointestinal disorders and psychiatric disorders, and FMT has been considered as an acceptable treatment option for IBS associated with anxiety or depression ( 31 , 32 ). Studies had found that alterations in gut microbiota composition existed in patients with either IBS, depression, or anxiety, alone or comorbid ( 33 ), and FMT could not only improve gastrointestinal symptoms but also show meaningful benefits in relieving anxiety and depression. Most scholars believed that the multiple effects of FMT on IBS patients with anxiety or depression should be attributed to the changes in the diversity and composition of the gut microbiota ( 34 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…With further research on IBS and the development of the theory of microbiota–gut–brain axis, the intestinal microbiota has been suggested as the pathophysiological basis of functional gastrointestinal disorders and psychiatric disorders, and FMT has been considered as an acceptable treatment option for IBS associated with anxiety or depression ( 31 , 32 ). Studies had found that alterations in gut microbiota composition existed in patients with either IBS, depression, or anxiety, alone or comorbid ( 33 ), and FMT could not only improve gastrointestinal symptoms but also show meaningful benefits in relieving anxiety and depression. Most scholars believed that the multiple effects of FMT on IBS patients with anxiety or depression should be attributed to the changes in the diversity and composition of the gut microbiota ( 34 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…The human gut microbiota comprise an enormous number of microorganisms, nearly 100 times larger than our own cells, and play crucial roles in human development, physiology, immunity, and nutrition, sometimes called the "second brain" (Dinan and Cryan, 2017;Sochocka et al, 2019). Continuous dynamic cross-talk between the gut and the brain is facilitated by neuronal, endocrine, metabolic, and immune pathways (Morais et al, 2021;Wilmes et al, 2021), which have been considered as the biological and physiological basis of psychiatric, neurodevelopmental, age-related, and neurodegenerative disorders such as AD. Gut microbiota and the brain communicate with each other via various routes which include: (i) regulating immune activity and the production of proinflammatory cytokines (e.g., IL-1β, IL-6, and IL-17A) or antiinflammatory cytokines (e.g., IL-4 and IL-10) that can either stimulate the hypothalamic-pituitary-adrenal axis to produce corticotropin-releasing hormone, adrenocorticotropin hormone and cortisol, or directly impact on central nervous system (CNS) immune activity; (ii) production of short-chain fatty acids (SCFAs), branched chain amino acids, and peptidoglycans; (iii) the production of neurotransmitters (e.g., acetylcholine, GABA, dopamine, and serotonin) that may enter circulation and cross the blood-brain barrier; (iv) modulating tryptophan metabolism and downstream metabolites, serotonin, kynurenic acid and quinolinic acid; (v) affecting vagus nerve and the enteric nervous system; (vi) impacting enterochromaffin cells by SCFAs and indole (Kennedy et al, 2017;Cryan et al, 2019;Morais et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Increased permeability of the GI lumen, commonly referred to as “leaky gut”, which also has been shown to lead to exaggerated inflammation ( Camilleri, 2019 ), has been identified in those suffering from affective, GI (e.g., inflammatory bowel disorders [IBD]), and cardiovascular disorders ( Ait-Belgnaoui et al., 2012 ; Bischoff et al., 2014 ; Novakovic et al., 2020 ). Similarly, it is common for those GI and cardiovascular disorders to have comorbid affective disorders ( Wilmes et al., 2021 ; Cohen et al., 2015 ). Given the high rates of inflammatory disorders among Veterans ( Tanielian et al., 2008 ; Breland et al., 2017 ), this is an important population within which to study the microbiota-gut-brain axis and physical and mental health.…”
Section: Discussionmentioning
confidence: 99%